Ecological impacts of the invasive plant Xanthium strumarium and the impacts of three aboveground herbivores on the invader. (November 2021) - Iqbal, Mazher Farid; Feng, Yu-Long; Feng, Wei-Wei; Liu, Ming-Chao; Lu, Xiu-Rong
Graphical abstract: Highlights: Invasive Xanthium strumarium negatively impacted co-occurring native plants. Three herbivore insects were found on the invader, reducing its growth significantly. The higher relative abundance of the invader was, the more the herbivores was. Natural enemies may gradually accumulate on invaders, inhibiting further invasions. The results provide evidence for the enemy release hypothesis. Abstract: Exotic plant invasions are generally assumed to negatively impact biodiversity of recipient communities. However, experimental evidence for this assumption is little, especially in developing countries. In addition, there is hardly applicable method to control invasive plants. Enemy release is often hypothesized to facilitate exotic plant invasions, thus re-association with natural enemies of invasive ranges may inhibit invasions of exotic plants, and these enemies may have the potential to be used as biological control agents for these invaders. To address above problems, we determined abundance of the invasive plant Xanthium strumarium, its impacts on co-occurring native plants, and abundances of three herbivores and their impacts on the invader at five sites in the rice tract of Punjab, Pakistan. Relative abundance of the invader varied greatly among the study sites, ranging from 3.5% to 50.4%. The invader significantly reduced abundance of co-occurring native plants at all study sites, and their richness and evenness at some sites with high abundances of the invader. The polyphagous insects Phenacoccus solenopsis, Podisus maculiventris and Spodoptera frugiperda were all found on the invader (not on crops) at all study sites, which significantly reduced growth of the invader. The abundance of P. solenopsis on the invader was much higher than those of P. maculiventris and S. frugiperda . The abundances of the herbivores were significantly higher at sites with high relative to low relative abundances of the invader. Our study indicates that natural enemies may accumulate on invasive plants with the increase of their abundance and/or invasion time, inhibiting further invasions, and provides evidence for enemy release hypothesis. More studies are needed to determine whether these herbivores, especially P. solenopsis, could be used as biological control agents for the invader.